Acacia sieberiana (Fabaceae) attenuates paracetamol and Bile Duct Ligation-Induced hepatotoxicity via modulation of biochemical and oxidative stress biomarkers - Watafua, Miriam; Ejiofor, Jane I.; Musa, Aminu; Ahmad, Mubarak Hussaini (Frontiers in Pharmacology, 2022)
Background: The plant Acacia sieberiana (Fabaceae) is traditionally used to manage hepatitis. This research work aims to investigate the hepatoprotective effectiveness of root bark extract of Acacia sieberiana (ASE) against paracetamol (PCM) and bile duct ligation (BDL)-induced hepatotoxicity. The phytochemical and median lethal dose (LD50) investigations were conducted. The rats were pre-treated with the ASE (250, 750, and 1,500 mg/kg) once daily via oral route for 7 consecutive days. On the 8th day, liver injury was initiated by PCM administration (2 g/kg). Similarly, in the BDL-induced liver injury, the animals were administered ASE (125, 250, and 380 mg/kg) intraperitoneally for 7 consecutive days. After 24 h, blood samples and hepatic tissues were obtained for biochemical and histopathological investigations. Results: Phytocomponents determination revealed glycosides, triterpenes, glycosides, saponins, tannins, flavonoids and alkaloids. The oral and intraperitoneal LD50 values of the ASE were >5,000 and 1,300 mg/kg, respectively. The ASE efficiently (p < 0.05) decreased the alanine transaminase (ALT) and aspartate transaminase (AST) levels and elevated the albumin and total protein (TP) levels. The direct bilirubin effectively (p < 0.05) decreased at 750 mg/kg. Besides, the extract efficiently elevated the glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT) in relation to the PCM hepatotoxic group. Also, the malondialdehyde (MDA) concentration was reduced by the ASE. Meanwhile, in the BDL–induced liver injury, the ASE remarkably (p < 0.05) declined the AST, ALP, bilirubin,and MDA. Besides, there was effective (p < 0.05) elevation in SOD, GPx and CAT in the ASE-treated groups. The morphology of liver tissue was preserved at 125 and 250 mg/kg ASE groups from BDL-induced necrosis and vascular congestion. Conclusion: The study shows that the ASE has hepatoprotective actions against liver damage by possible modulation of biochemical and oxidative stress biomarkers.